Kemampuan Komunikasi Matematis Siswa Terhadap Materi Persamaan Linear Satu Variabel : Kemampuan Komunikasi Matematis Siswa Terhadap Materi Persamaan Linear Satu Variabel - Nurwita, Faizah (Program Studi Pendidikan Matematika jenjang Magister, FMIPA, Universitas Negeri Jakarta, 2020)
This study aims to describe the mathematical communication skills of junior high school students class VII B at SMP N 3 Sungai Tebelian, Sintang, West Kalimantan. In addition, to examine the communication problems faced by students during learning on the One Variable Linear Equation material. The research method used is the description method with the research subject of 25 students. This research instrument uses a response questionnaire to determine students' mathematical communication skills with 12 questions that are distributed directly via offline. There are six indicators of mathematical communication skills analyzed but only one indicator can be achieved with the percentage of student questionnaire results obtained 3.5%.